Molecular Interaction Study of Antibiotic Doxycycline Hyclate with Linoleic Acid - C.ROUMANA; G. VELRAJ (International Journal of Pharma and Bio Sciences, 2010)
Molecular Interaction of antibiotic Doxycycline hyclate with unsaturated fatty acid, the linoleic acid have been investigated using dilute solution viscosity and ultrasonic techniques at ambient temperature 303 and the physiological temperatures 310 and 313K in the presence of solvent ethyl methyl ketone. The temperatures 310 and 313K are favouring interaction between Doxycycline Hyclate and linoleic acid. The interaction between the antibiotic and the linoleic acid is found on the basis of solute-solute and solute-solvent interactions. Thus the antibiotic exhibits high structural specificity and the structure of the drug play an important role in exhibiting liphophilic interactions.